Do strategic interaction effects drive excess capital financing of banks? - Genevieve Nelson; Mia Renee Herløv Jørgensen (Danmarks Nationalbank, 2021)
In this memo we find empirical evidence consistent with the hypothesis that banks act strategically to finance themselves through similar levels of excess capital to their competitors. We find that this channel is a significant driver of banks' choice of excess capital but not the most important one.
Keywords: 330; Macroprudential policy; Connectedness